Efektivitas Pelatihan Kepemimpinan Administrator (PKA) oleh BPSDM Provinsi Jawa Barat Tahun 2023 - Zamzami, Mochamad Fachri Rizky; Sagita, Novie Indrawati; Adinda FA, Jovanscha Qisty (Universitas Batanghari, 2024)
The State Administration Institute of the Republic of Indonesia (LAN) has issued Decree of the Head of the State Administration Agency Number 2 of 2023 concerning Guidelines for Implementing Structural Leadership Training Activities which is the basis for holding education and leadership training activities for administrator officials. This research will discuss the 2023 Class IV Administrator Leadership Training (PKA) activities which were held in order to meet managerial competency standards in structural civil servant positions. The method used in this research is a qualitative method to analyze the effectiveness of implementing structural leadership training activities which is based on measuring sources, processes and targets. Data collection techniques in this research were carried out through interviews, observation, literature study and documentation. The results of this research show that the implementation of managerial leadership training for the position of Administrator (PKA) Class IV in 2023 carried out by the West Java Province Human Resources Development Agency is hampered by the limited number of class observers, the ability of participants who have not yet adapted to the learning methods applied, as well as disrupting participants' concentration because they had to carry out work tasks in their work unit in between training activities, so that aspects of the process did not run optimally.